Emotional Exhaustion and Teaching Performance: An Approach to Burnout Syndrome in University Professors - Bozano-Rivadeneira, Esteban (2026)
This study analyzes the influence of burnout syndrome on the performance of university teachers, based on data collected at the Faculty of Philosophy, Letters, and Education Sciences of the Central University of Ecuador. The central problem addressed by the manuscript is the lack of attention given to the emotional health of education professionals, who constitute one of the populations most exposed to work-related stress. In response to this problem, the authors propose an approach to assess the impact of factors such as emotional exhaustion, personal fulfillment, and depersonalization on faculty performance. It contextualizes the current state of studies associated with the topic through a brief overview of the state of the art and the conceptualization of the variables studied. This is a quantitative, cross-sectional study based on descriptive and correlational methods, as well as data provided by a sample of professors. Data collection involved interviewing teachers using the Maslach Burnout Inventory and the Competency-Based Teacher Evaluation Questionnaire (EDBC). Relevant findings include the weak relationship between the study variables, the importance of considering sociodemographic qualities such as the gender and age of participants when identifying possible causes of burnout, and the implication of professional experience in the development of strategies for preventing and coping with work-related stress.